ADMINISTRATIVE PROCESSES BASED ON THE CREATIVE APPROACH OF THE EDUCATIONAL PROCESS IN HIGHER EDUCATION (TAMADDUN NURI JURNALI, 2024)
In this article, a lot of scientific information is given about the processes of management of the educational process in higher education based on a creative approach. In addition, attention is paid to the integration of creative approaches in the administrative processes of higher education institutions, their impact on improving the educational experience and institutional efficiency. This article explores a variety of strategies, including participatory decision-making, flexible policy design, and the innovative use of technology, to show how creative management can address contemporary challenges in higher education.